Family Strategies in Quest for Power: Examples from Medieval Zadar (11^th-13^th Century) - Nikolić, Zrinka (2001)
The theme of the paper is the development of family strategies in search for power in medieval Dalmatian town of Zadar. It deals with families from upper circles in Zadar, and concerns the period between the eleventh and the thirteenth century, before the closing of the town councils and legal confirmation of belonging to the noble class. In the above mentioned period the Zadar families were using different methods to reach and maintain the elevated status in society since it was not entirely guarranted by birth. Different strategies were employed: economic and politic activites, matrimonial connections, affiliations to ecclesiastical and lay institutions, etc. All of these are explored, mainly on published archival sources although, some unpublished material from the Archive from Zadar are used as well.